PERBEDAAN TINGKAT KESEMBUHAN ULKUS DIABETIK MENGGUNAKAN PENCUCI LUKA NACL 0,9% DENGAN PIPER CROCATUM - Martina Evlyn Romauli Hutahaean; Amin Sidik; Dewi Astuti Pasaribu; Elyani Sembiring (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Diabetic wounds, a condition experienced by diabetics due to impaired blood flow, neuropathy, prolonged inflammation, and excessive bacterial infection can result in tissue death (necrosis) which increases the risk of amputation. The wound washing process plays a very important role in determining the quality of wound healing. Piper Crocatum leaf contains flavonoids, saponins, alkaloids, tannins, and essential oils as antidiabetics and antibacterials. There are not many clinical studies that directly compare the effectiveness of NaCl 0.9% and Piper crocatum in healing diabetic ulcers. This study aims to analyze the difference in wound healing rates in diabetic ulcer patients before and after treatment, which involves the use of NaCl and piper crocatum decoction. This type of research is quasi-experimental with accidental sampling technique with the criteria of controlled blood sugar levels and non-smoking in 5 diabetic ulcer patients who underwent wound washing treatment using 0.9% NaCl, and 5 diabetic ulcer patients who received wound washing treatment with piper crocatum decoction. The results of the paired t-test (p<0.000) showed that there was an effect of wound washing using 0.9% NaCl and piper crocatum on the healing rate of diabetic ulcers in each group. The healing rate was measured using Bates Jensen Wound Assessment Tool.